Perceived Social Support and Parental Stress Among Married Couples: An Exploratory Study - Mora, Balanji Reddy; Meghana, P. (Journal of Social Science and Humanities, 2026)
In this research paper, the researcher describes a mixed-method study designed to explore perceived social support and parental stress among married couples within the Indian context. Specifically, a thematic analysis of open-ended responses was conducted to questions about the extent of social support received by the participants with respect to parental stress. A correlation study was also conducted on 101 participants to understand the relationship between social support and parental stress, an independent sample T-test to check gender differences, and ANOVA to check mean differences between social support and parental stress, the tool used included Multidimensional Scale of Perceived Social Support (MSPSS) and Parental Stress Scale (PSS). The qualitative results indicate that a moderately negative correlation exists between the variables perceived social support and parental stress among married couples. Thus, higher levels of social support lead to lower levels of parental stress. Additionally, a significant gender difference exists in parental stress among married couples, with females reporting greater levels of stress than males. Whereas, no significant gender difference exists with respect to perceived social support among married couples. Whereas, the findings of mean differences in parental stress among married couples based on the number of children they have, indicate that there is no significant difference. The qualitative analysis, on the other hand, identifies major themes and implements that holistic care approaches along with empowerment systems must be encouraged if the complexities of parenthood have to be dealt with adequately. Implications, limitations, and directions for further research are discussed.